A simple and effective expert system for schizophrenia detection. (2015) - Singh, Pawan Kumar; Sarkar, Ram
Expert Systems are computer programs that are derived from a branch of computer science research called artificial intelligence (AI). But, most progress till date in AI has been made in the area of problem solving - concepts and methods for building programs that reason about problems rather than calculate a solution. Schizophrenia is a complex mental disorder which is characterised by a wide range of signs and symptoms that reflect disturbances in cognitive, emotional, perceptual and motor processes. Schizophrenia ranks among the top 10 causes of disability in developed countries worldwide (http://tmm.trends.com). In this paper, an attempt has been made to develop an expert system which can detect a disease called Schizophrenia at an earlier stage in human brain.